Physico-Mechanical, Nutritional, and Sensorial Properties of Gluten-Free Chips with Almond Powder Dried Using Different Drying Methods - Altay, Kadriye; Rayman Ergün, Ahsen; Şahin, Müge; Deliboran, Aişe (Food Science and Engineering, 2023)
In this study, newly formulated gluten-free chips with almond powder were produced. Almond powders were obtained using 3 different drying methods: oven drying, freeze drying, and microwave drying. This study aimed to determine the effect of drying almond powders used in gluten-free chip production using different drying methods and then adding different ratios (10% and 30%) of these powders to the chips on the physicochemical, textural, mineral, and sensory properties of the chips. The physical, textural, mineral, and sensory analyses were then carried out. The moisture content values of the chips with almond powder were < 6.32% and the water activity values were < 0.300. Adding almond powder increased the total fat and protein content of the chip samples. The protein content of the gluten-free chips increased by 34.69-257.14% compared to the control sample and the highest protein content (1.75%) was determined in the samples containing 30% of the almond powder obtained using the microwave drying method. The hardness of the gluten-free chips decreased by increasing the almond powder. The addition of the almond powder to the chip formulation generally increased the B, Cu, Mn, and Zn contents of the gluten-free chips. All chip samples enriched with almond powder showed similar overall acceptability scores (5.00-6.89).